0

I know that ∀x∈A P(x) is only equivalent to ∀x(x∈A -> P(x)), but why isn't it equivalent to ∀x(x∈A /\ P(x))? I can use the laws in logic to compare the two, but I want an intuitive reason as to why this is the case. To me, it seems logical that if ∃x∈A P(x) equivalent to ∃x(x∈A /\ P(x)), then ∀x∈A P(x) is equivalent to ∀x(x∈A /\ P(x)), but I'm definitely wrong, so I'm asking for a new way to see it.

1
3

∃x∈A P(x) - "There exists an X in A that is P(X)".

∀x∈A P(x) - "All X in A are P(X)".

In the former statement, you use the "in A" part to provide more information about some specific X. This is expressed as a predicate (x∈A in this case) which is conjuncted with the other predicates representing the rest of your knowledge.

In the latter, you use the "in A" part to provide a condition under which P(X) holds, which is expressed as an implication.

Or, in other words - if there exists a cat that is black, there exists something that is a cat and is black. But if all cats are black, you can't say everything in the whole world is a cat and is black - but you can say that everything is black if it's a cat.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.